Antivirulence DsbA inhibitors attenuate Salmonella enterica serovar Typhimurium fitness without detectable resistance. Issue 4 (10th February 2021) - Dhouib, Rabeb; Vagenas, Dimitrios; Hong, Yaoqin; Verderosa, Anthony D.; Martin, Jennifer L; Heras, Begoña; Totsika, Makrina
ABSTRACT: Inhibition of the D iS ulfide B ond (DSB) oxidative protein folding machinery, a major facilitator of virulence in Gram‐negative bacteria, represents a promising antivirulence strategy. We previously developed small molecule inhibitors of DsbA from Escherichia coli K‐12 (EcDsbA) and showed that they attenuate virulence of Gram‐negative pathogens by directly inhibiting multiple diverse DsbA homologues. Here we tested the evolutionary robustness of DsbA inhibitors as antivirulence antimicrobials against Salmonella enterica serovar Typhimurium under pathophysiological conditions in vitro. We show that phenylthiophene DsbA inhibitors slow S . Typhimurium growth in minimal media, phenocopying S . Typhimurium isogenic dsbA null mutants. Through passaging experiments, we found that DsbA inhibitor resistance was not induced under conditions that rapidly induced resistance to ciprofloxacin, an antibiotic commonly used to treat Salmonella infections. Furthermore, no mutations were identified in the dsbA gene of inhibitor‐treated S . Typhimurium, and S . Typhimurium virulence remained susceptible to DsbA inhibitors. Our work demonstrates that under in vitro pathophysiological conditions, DsbA inhibitors can have both antivirulence and antibiotic action. Importantly, our finding that DsbA inhibitors appear to be evolutionarily robust offers promise for their further development as next‐generation antimicrobials against Gram‐negative pathogens.